2019
DOI: 10.1016/j.electacta.2018.11.173
|View full text |Cite
|
Sign up to set email alerts
|

When supporting electrolyte matters – Tuning capacitive response of graphene oxide via electrochemical reduction in alkali and alkaline earth metal chlorides

Abstract: The ability to tune charge storage properties of graphene oxide (GO) is of utmost importance for energy conversion applications. Here we show that electrochemical reduction of GO is highly sensitive to the cations present in the solution. GO is reduced at lower potential in alkali metal chloride solutions than in alkaline earth metal chlorides. During the reduction, capacitance of GO increases from 10 to 70 times. Maximum capacitances of reduced GO are between 65 and 130 F g −1 , depending on the electrolyte a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…The highest observed capacitances (83.5 and 98.9 F g −1 for DC 2 and ED 1 , respectively) are within the specific capacitance range reported for chemically reduced GO when examined in organic and aqueous solutions (99 to 135 F g −1 ) 62 and electrochemically produced rGO when examined in alkali and alkaline earth metal chlorides (maximum capacitances between 65 and 130 F g −1 ). 63 The cycle life during 500 charge/discharge cycles of the DC 5 and ED 5 coatings on the GCP electrodes in 1.0 M KOH was examined at a current density of ±1.6 mA cm −2 and plots of the specific capacitance vs cycle number are shown in Fig. S3.…”
Section: Resultsmentioning
confidence: 99%
“…The highest observed capacitances (83.5 and 98.9 F g −1 for DC 2 and ED 1 , respectively) are within the specific capacitance range reported for chemically reduced GO when examined in organic and aqueous solutions (99 to 135 F g −1 ) 62 and electrochemically produced rGO when examined in alkali and alkaline earth metal chlorides (maximum capacitances between 65 and 130 F g −1 ). 63 The cycle life during 500 charge/discharge cycles of the DC 5 and ED 5 coatings on the GCP electrodes in 1.0 M KOH was examined at a current density of ±1.6 mA cm −2 and plots of the specific capacitance vs cycle number are shown in Fig. S3.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, in order to benefit from both GO and graphene, a balance between their desirable properties is necessary [ 20 ]. Recently, a precise modification of oxygen functionalities on graphene and the graphene oxide basal plane was proposed, in order to finely tune its properties [ 9 , 11 , 29 , 30 , 31 , 32 ]. The main challenge is to carry out a precise reduction process (using different reducing agents or reduction conditions), with the possibility of controlling both the reduction degree (the OFGs’ content) and the selectivity of the key OFGs’ removal [ 11 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of GO layers can be achieved using thermal, chemical, photoreduction, microwave irradiation and electrochemical methods [ 6 , 9 , 32 , 38 ]. Electrochemical reduction, a room temperature process, is considered a green route, since neither toxic chemicals (which are harmful to both humans and the environment, and can contaminate the final product) nor high temperatures are employed during the electrochemical reduction process [ 10 , 16 , 21 , 29 , 39 ]. Moreover, the simple manipulation of the electrochemical reduction process of the graphene oxide can be achieved through controlling the potential, reduction time and electrolyte choice [ 10 , 33 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…When looking at carbon materials, just recently it was demonstrated that alkali metal and earth alkaline metal cations have striking effect on the process of electrochemical reduction of graphene-oxide. 16 This process takes place at potentials where cations from supporting electrolyte cannot be reduced, so the effect was ascribed to the interaction of M + and M 2+ with oxygen functional groups, resulting with their activation towards the reduction process. Hence, one might expect that the effect of alkali metal cations from supporting electrolyte could be expected in some other cases, like ORR.…”
Section: Introductionmentioning
confidence: 99%